2018
DOI: 10.1055/s-0038-1675582
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline Use in Neonates: 5-Year Experience of a Tertiary Center

Abstract: The off-label use of tigecycline to treat serious infections has been reported in pediatric patients. We report four newborn infants diagnosed with sepsis caused by extensively drug-resistant Klebsiella pneumoniae and successfully treated with tigecycline. If no alternative drugs are available, tigecycline may be considered as an option for nosocomial infections even in newborn infants. However, further reports are needed to establish its efficacy and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In pediatric patients, tigecycline is not recommended because it can lead to gastrointestinal adverse events (nausea, vomiting, diarrhea, and acute pancreatitis), prolonged coagulation times, mild increase in transaminases, direct bilirubinemia, thrombocytopenia, and permanent discoloration of the teeth, although studies have reported the use of tigecycline combined with other antimicrobial agents in the treatment of MDR infection in newborn infants and children. 17-24…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pediatric patients, tigecycline is not recommended because it can lead to gastrointestinal adverse events (nausea, vomiting, diarrhea, and acute pancreatitis), prolonged coagulation times, mild increase in transaminases, direct bilirubinemia, thrombocytopenia, and permanent discoloration of the teeth, although studies have reported the use of tigecycline combined with other antimicrobial agents in the treatment of MDR infection in newborn infants and children. 17-24…”
Section: Discussionmentioning
confidence: 99%
“…In pediatric patients, tigecycline is not recommended because it can lead to gastrointestinal adverse events (nausea, vomiting, diarrhea, and acute pancreatitis), prolonged coagulation times, mild increase in transaminases, direct bilirubinemia, thrombocytopenia, and permanent discoloration of the teeth, although studies have reported the use of tigecycline combined with other antimicrobial agents in the treatment of MDR infection in newborn infants and children. [17][18][19][20][21][22][23][24] Thus, CAZ-AVI 50 (40/10) mg/kg IV q8h dosage was initially chosen (dosage for patients aged 3 months to < 6 months); however, after two days, it was adjusted based on renal function to 23.75 mg/kg IV q48h, returning to the initial dose on the fifth day. Our patient was treated with CAZ-AVI for 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of all patients was favorable without serious adverse events. Interestingly, after the first week of treatment, all neonates presented with thrombocytopenia related to the drug, with PLT gradually returning to normal values after the end of therapy [ 120 ].…”
Section: Other Novel or Repurposed Antibacterial Agentsmentioning
confidence: 99%